The substance of interaction: design and policy implications of NGO- government projects in India - Alsop, Ruth; Arya, Ved (International Food Policy Research Institute, 1999)
Collaboration between government and non-government organizations has been a recurrent feature of many development interventions in India. This paper is based on case studies of 11 such programs.